PENGARUH CORPORATE SOCIAL RESPONSIBILITY, LEVERAGE, SIZE TERHADAP PROFITABILITAS (STUDI KASUS PADA PERUSAHAAN MANUFAKTUR DI BEI TAHUN 2018-2020) - Muhdin, Muhdin; Sarmo, Sulaiman; Negara, Iwan Kusuma (Jurnal Ilmiah Akuntansi Indonesia, 2024)
This research analyzes the influence of Corporate Social Responsibility, leverage, Size on profitability. The latest thing in this research is that the research was carried out during the Covid-19 pandemic. Apart from that, this research will have a big impact on companies, investors and also the environment, because it encourages investors not only to look at the return on assets in published financial reports but also to pay attention to the implementation of CSR, leverage, and company size during the pandemic. The type of research used in this research is associative research with causal relationships, namely causal relationships where there are variables that are influenced (Dependent). The type of data used in this research is quantitative data. The population in this research are manufacturing companies listed on the Indonesia Stock Exchange with a research period ranging from 2018-2020 with a sampling method using purposive sampling so that the total sample is 180 samples. Report preparation: carried out by collecting secondary data taken on the website www.idx.co.id using the documentation method. The data will be analyzed according to the method that will be used in this research. Data analysis was carried out using descriptive statistics. Data analysis was carried out in several stages, namely testing classical assumptions. The classical assumption tests carried out are: Normality test, multicollinearity test, autocorrelation test, and heteroscedasticity test. Next, data analysis was carried out using multiple regression techniques. The research results show that CSR has a negative effect on profitability, while leverage and company size have no effect on profitability. These results have implications if during the pandemic the company carries out a lot of CSR, then the company's profitability will decrease.